2004
DOI: 10.1063/1.1637919
|View full text |Cite
|
Sign up to set email alerts
|

Magnetic islands and plasma rotation in the Tokamak Chauffage Alfvén Brésilien tokamak

Abstract: Collisional plasma rotation in the Tokamak Chauffage Alfvén Brésilien (TCABR) tokamak [J. H. F. Severo, I. C. Nascimento, V. S. Tsypin, and R. M. O. Galvão, Nucl. Fusion 43, 1047 (2003)] has been experimentally studied. It was found that the measured plasma poloidal rotation velocity agrees within error limits with neoclassical theoretical predictions, and toroidal velocity with experimental results obtained in analogous tokamaks, almost everywhere along the minor radius r, except for measurements at r/a≃0.56 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
13
0

Year Published

2005
2005
2016
2016

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 16 publications
(16 citation statements)
references
References 15 publications
3
13
0
Order By: Relevance
“…The fact these two curves do not converge when the island width saturates can be interpreted as an indication the pressure profile inside the island is not completely flat. Actually, previous measurements in TCABR have shown that not only the poloidal rotation varies with radius [11,12], but also that the temperature profile is not flat across the islands [30]. Similar results have been obtained in other experiments; however ours presents a quite clear example for the case in which one can assure that there is no driven toroidal rotation, i.e., it is entirely intrinsic.…”
Section: Disruptive Dischargessupporting
confidence: 87%
See 3 more Smart Citations
“…The fact these two curves do not converge when the island width saturates can be interpreted as an indication the pressure profile inside the island is not completely flat. Actually, previous measurements in TCABR have shown that not only the poloidal rotation varies with radius [11,12], but also that the temperature profile is not flat across the islands [30]. Similar results have been obtained in other experiments; however ours presents a quite clear example for the case in which one can assure that there is no driven toroidal rotation, i.e., it is entirely intrinsic.…”
Section: Disruptive Dischargessupporting
confidence: 87%
“…This is even more valid around the position of the rational surface. In fact, previous measurements of the impurity rotation at the plasma edge of TCBR have shown that the neoclassical prediction is reasonably verified experimentally [11,12]. …”
Section: Methodsmentioning
confidence: 55%
See 2 more Smart Citations
“…This phenomenon shows a joint rotation of the island and surrounding plasma which is claimed in. [20][21][22] The amplitude of high frequency fluctuations (>20 kHz) decrease by a positive bias application as in the ISTTOK 2 , DIII-D 23 and KT-5C 24 tokamaks furthermore negative bias has been investigated but it has no obvious effect on the global properties of plasma.…”
Section: Experiments and Discussionmentioning
confidence: 99%